Physical fitness of prospective pilgrims: Hajj and Umrah gymnastics - Sukendro Sukendro; Fadli Ihsan; Palmizal. A; Ugi Nugraha; Sugih Suhartini; Yonifia Anjanika; Fitri Khairunnisa (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Background: Physical fitness is crucial for the smooth execution of Hajj and Umrah, as approximately 70% of the pilgrimage involves intense physical activity, including walking long distances, prolonged standing, and exposure to extreme temperatures. Many prospective pilgrims lack optimal physical readiness, increasing their risk of fatigue and health issues. Effective exercise strategies are needed to enhance their endurance before departure.